2017
DOI: 10.2334/josnusd.16-0878
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of mature adipocyte-derived dedifferentiated fat cells into three-wall defects in the rat periodontium induces tissue regeneration

Abstract: The transplantation of dedifferentiated fat (DFAT) cells in combination with poly(d,l-lactic-co-glycolic acid) (PLGA) scaffolds has previously been proven as an effective approach in promoting periodontal tissue regeneration in a rat fenestration defect model. The aim of this study was to assess the regenerative potential of DFAT cells in a rat model of three-wall periodontal bone defect. Three-wall bone defects were created bilaterally on the mesial side of rat maxillary first molars and were either left untr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…Two types of adipose-derived stem cells (ASCs), identified as MSCs and DFAT cells, can be isolated from subcutaneous adipose tissues or buccal fat pads [22][23][24][25][26][27]. Several studies reported that DFAT cells and ASCs potentially contribute to regeneration of periodontal tissue in animal models [22,24,27]. However, previous results suggest that osteoblastic differentiation potential is greater for DFAT cells than for ASCs [22], which is consistent with data from other studies [34].…”
Section: Introductionsupporting
confidence: 76%
See 3 more Smart Citations
“…Two types of adipose-derived stem cells (ASCs), identified as MSCs and DFAT cells, can be isolated from subcutaneous adipose tissues or buccal fat pads [22][23][24][25][26][27]. Several studies reported that DFAT cells and ASCs potentially contribute to regeneration of periodontal tissue in animal models [22,24,27]. However, previous results suggest that osteoblastic differentiation potential is greater for DFAT cells than for ASCs [22], which is consistent with data from other studies [34].…”
Section: Introductionsupporting
confidence: 76%
“…After about 1 week, the medium was replaced with growth media, and the flasks were inverted so that the cells were on the bottom of the culture flasks ( Fig. 1) [22][23][24][25]. The initial DFAT cells, referred to as passage 0 (P0), were passaged at 80% confluence.…”
Section: Preparation Of Dedifferentiated Fat Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…DFAT cells are, perhaps somewhat surprisingly, not currently being used as a cell culture model for adipocyte biology, although several recent studies have utilized these cells in experimental stem cellbased therapies (Mikrogeorgiou et al, 2017;D. Suzuki et al, 2017).…”
Section: Dedifferentiated Fat (Dfat) Cellsmentioning
confidence: 99%